Student Worksheet (LKPD) Development Based on Local Wisdom in the Making of Teak Leaf Extract as a Natural Indicator of Acid-Base - Mukhtar, Raine Ramdhanya; Hairida, Hairida; Enawati, Eny; Masriani, Masriani; Erlina, Erlina (Universitas Pendidikan Mandalika, 2024)
This study aims to determine the level of feasibility and response of teachers to the development of student worksheets (LKPD) based on local wisdom on the use of teak leaves as a natural indicator of acid-base acid. This research method is Research and development (R&D) or a development method with the ADDIE research model which consists of analysis, design, development and evaluation. The subject of this research is LKPD which is validated by 2 experts in the fields of materials and graphics and linguistics. This study was also to determine the responses of 5 chemistry teachers from Alor district, East Nusa Tengggara and Singkawang city, West Kalimantan by using data collection instruments in the form of validation sheets and teacher response questionnaires with indirect communication data collection techniques. The results of data processing showed that LKPD products based on local wisdom had a validity level of 83.12% and the results of the educator response test of 97.5% with each category very feasible.